Efficient organic enrichment from sludge filtrate via a forward osmosis membrane process. Issue 4 (August 2020) - Chang, Jiang; Qiu, Haoran; Wang, Jiawei; Lin, Rijia; Hernandez, Byron Villacorta; Ji, Chunmiao; Liu, Guoliang; Zhao, Xuan; Ge, Lei
Graphical abstract: Highlights: This work proposed the novel process to treat the intractable sludge filtrate. Forward osmosis process can enrich organic matter with rejection rates over 90%. High membrane permeability recovery can be achieved after simple offline washing. Abstract: Anaerobically digested sludge filtrate after thermal hydrolysis pretreatment (THP-AD) requires large plant and operational costs for post-treatment and re-utilization. This paper reports the innovative forward osmosis (FO) membrane process to enrich organic matter from such a digested sludge filtrate. The proposed membrane separation process can reduce the operational load and environmental dependence of waste sewage treatment plants and may provide a new way for the treatment of THP-AD sludge filtrate. In this study, a cost-effective draw NaCl solution was selected for the FO process. The sensitivity of membrane operational conditions including membrane orientation, system temperature, system flow rate and concentrations of draw solution was investigated and correlated with the FO processing performance. FO mode is a clever choice to reduce the deposition of pollutants on the membrane's surface, and improve the recovery performance of the membrane. The permeation flux of the THP-AD sludge digestion system decreased more rapidly due to the membrane pollution as well as to the decreasing of driving force caused by the dilution of the draw solution and the concentration of the feed solution. The concentration factor of digested sludge filtrate after FO process was more than five, and the rejection rates of organic and inorganic matter were above 92.5%. The membrane permeability recovery after the offline washing reached up to 98.4% and showed high efficiency at removing membrane fouling substances and at reactivating the membrane. The proposed FO process has potential as an alternative and practical method for treating and utilizing intractable sludge filtrates, conducive to the development of sustainable wastewater plants.